2019
DOI: 10.1007/s11661-019-05333-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Powder Recycling in Electron Beam Melting on the Surface Chemistry of Alloy 718 Powder

Abstract: Process-induced degradation of the powder feedstock in additive manufacturing may have a negative influence on the final properties of built components. Consequently, it may lower the cost-effectiveness of powder bed additive manufacturing, which relies on recycling of the nonconsumed powder. This is especially the case for production of high-performance aero engine components where high material and process reliability is required. This study comprises a detailed investigation on the degradation of Alloy 718 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 23 publications
1
20
0
3
Order By: Relevance
“…Figure 3 shows the surface of a powder sample collected before build cycle number 30. As was already described in previous research, [23,24] a significant part of the re-used Alloy 718 powder surface is covered by Al-rich oxide particulate features that have formed during exposure of the powder to the process and the environment in the EBM build chamber. In Reference 24, it was also shown that the oxide particulates are confined to the powder surface.…”
Section: A Powder Characterizationmentioning
confidence: 62%
“…Figure 3 shows the surface of a powder sample collected before build cycle number 30. As was already described in previous research, [23,24] a significant part of the re-used Alloy 718 powder surface is covered by Al-rich oxide particulate features that have formed during exposure of the powder to the process and the environment in the EBM build chamber. In Reference 24, it was also shown that the oxide particulates are confined to the powder surface.…”
Section: A Powder Characterizationmentioning
confidence: 62%
“…From EDS analysis, the oxidation features were identified as rich in Al and Cr. The formation of Al-based oxides on Alloy 718 powders has already been reported after powder recycling in electron beampowder bed fusion (EB-PBF) [2].…”
Section: Resultsmentioning
confidence: 91%
“…Among the materials processable by L-PBF today, many are sensitive to these high temperatures that promote diffusiondriven processes such as oxidation. Rich in Ti, Al, Cr and other elements of high affinity for oxygen [2,3], these materials are likely to form stable oxide species, which are then transferred to the produced parts whose mechanical properties can be compromised. To limit these harmful consequences, an inert gas flow (Ar) covers the build area to remove impurities close to the melt pool and heated material.…”
Section: Introductionmentioning
confidence: 99%
“…If not reduced, these more stable oxsides remain within the consolidated sample 4–6 . Similar correlations have been drawn within the powder bed fusion AM processes, but these have mostly concerned powders that have been recycled 7–9 . There is hence a lack of published papers focusing on the surface oxide of original powder and the effect of atomizing media on surface chemical composition of the powder in the field of additive manufacturing.…”
Section: Introductionmentioning
confidence: 71%